Sustainable Environment: Green Human Resource Management Practices and Green Organisational Behaviour in Pakistani Hotels - Muhammad Ibrahim Khalil (Research Synergy Foundation Press, 2023)
This study investigates the attitudes towards sustainable practices in Pakistani hotels and explores the constructs of Green HRM Practices (GHRMP), Green Organizational Behavior (GOB), and Sustainable Environment (SE) as reliable and valid measures of these attitudes. A partial least squares structural equation modeling (PLS-SEM) and ecocritical analysis of the language were used to describe the environment and the values and attitudes expressed towards it was conducted, providing valuable insights into the cultural understanding of the natural world and our place within it. The study's results show that Pakistani hotels have a positive attitude towards sustainable practices, with a majority of respondents holding positive views towards GHRMP and GOB, and a slight majority leaning towards a neutral stance. The study also found that the majority of respondents consider the sustainable environment in Pakistani hotels to be important and believe it is necessary to take steps towards an eco-friendlier environment. The constructs of GHRMP, GOB, and SE were found to be reliable and valid measures of attitudes towards sustainable practices in Pakistani hotels, with strong associations between the items in the constructs and high levels of internal consistency. Discriminant validity was also established, indicating good discriminant validity between the constructs. Overall, the study's findings suggest that promoting green HRM practices and encouraging green organizational behavior can lead to improved environmental sustainability practices and business performance in Pakistani hotels. These results have significant implications for the hospitality industry in Pakistan and can help future research and policy decisions aimed at promoting to invest in renewable energy sources and use environmentally friendly products to reduce their impact on the environment.